An Analysis of Speech Act in Doctor Strange in the Multiverse of Madness Movie - Jatmiko, Agus jatmiko; Agustina, Eka; Zulaikah, Zulaikah (English Education Program, Education Faculty, Universitas Nurul Huda, 2022)
This study aims to classify the illocutionary speech acts according to Searle in the dialogue of Doctor Strange In The Multiverse Of Madness Movie, and to find the meaning contained in each illocutionary speech act according to. Searle's classification in the film Doctor Strange In The Multiverse Of Madness Movie. The method used in this research is descriptive analysis method by collecting conversations between characters in Doctor Strange In The Multiverse Of Madness Movie, researching them by looking at and considering the context behind the speech, then interpreting the meaning descriptively. The results of this study were 5 types of illocutionary speech acts according to Searle's classification found in the film sen Doctor Strange In The Multiverse Of Madness Movie, namely Representatives, Directives, Expressives, Commissives and Declarations. The Directives type serves dominant frequency of all four types of illocutionary speech acts. There were 32 data (48.48%) containing directives type. The second position was Representatives type. There were 22 data, it was 33,33%. The third position was Expressives type. There were 9 data (13.63%). The four position was Commissives type. There was 1 data, it was 01,51%. The lowest-rank frequency of type of illocutionary speech acts are the order Declarations type with 2 data (03.44%).